Quality of life and self-esteem in elderly patients who did or did not have cosmetic surgery - Lenise Maria Spadoni-Pacheco; Gustavo Azevedo Carvalho (Revista Brasileira de Cirurgia Plástica)
Introduction: The reality of aging has caught up with the field of plastic surgery, shown by the growth in the number of elderly patients who undergo cosmetic surgery (CS). To evaluate its importance in elderly women, this study examined differences in quality of life and self-esteem among those who did or did not undergo CS. Methods: This casecontrol study included 25 elderly women who underwent CS and a control group of 25 elderly women who did not undergo CS; the groups were matched by socioeconomic data. Assessment methods included the Mini-Mental State Examination, a quality of life (QOL) questionnaire (World Health Organization Quality of Life-Bref), the Rosenberg Self-Esteem Scale, and a questionnaire developed for the study of sociodemographic data, motivation, and satisfaction with CS. Results: The mean age was 67.26 years, with a mean of 9.96 years of education. The most common surgeries were abdominoplasty and blepharoplasty. The most common motivations were physical discomfort, desire to improve QOL, and dissatisfaction with self-image. No subjects were found to have low self-esteem and the level of satisfaction with personal or social life was high. There was no difference in QOL or self-esteem between the 2 groups. Conclusion: Physical and psychological motivations cause the elderly to undergo CS. There was no difference in QOL or self-esteem among elderly women who did or did not have CS. Elderly women who underwent CS showed high levels of satisfaction with their personal and social life.